LLMOps: Operationalizing Language Models for the Enterprise - Suruchi Shah (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article explores the emerging field of LLMOps (Language Model Operations), a specialized branch of MLOps focused on deploying and managing large language models (LLMs) in production environments. The article examines the LLM lifecycle, challenges in scaling LLMs, essential LLMOps tooling, best practices for effective management, and future trends. Drawing on recent industry studies and statistics, it highlights the growing significance of LLMOps in enterprise AI applications, its potential to streamline operations and reduce costs, and its role in addressing critical issues such as model performance, scalability, data privacy, and ethical AI deployment